EFFICACY OF VACUUM ASSISTED CLOSURE IN MANAGEMENT OF OPEN WOUNDS AS COMPARED TO MOIST WOUND DRESSING-EXPERIENCE AT CMH RAWALPINDI: Management of Open Wounds Vs Moist Wound Dressing - Iqbal, Muhammad Nouman; Noor, Mudassar; Sajid, Muhammad Tanveer; Ahmed, Zulfiqar; Iqbal, Muhammad Hatif; Ahmed, Muhammad (Pakistan Armed Forces Medical Journal, 2016)
Objective: To compare the efficacy of vacuum assisted closure (VAC) therapy against regular moist wound dressings in reducing the surface area of open chronic wounds by at least 5 mm2 in terms of early closure of wound. Study Design: Randomized controlled trail. Place and Duration of Study: This study was conducted at general surgery department CMH/MH Rawalpindi from Jun 2011 to Dec 2011 over a period of 06 months. Material and Methods: A total of 278 patients (139 in each group) were included in this study. Group A received VAC therapy while moist wound dressings applied in group B. Results: Mean age was 54.9 ±7.2 and 53.4 ± 8.9 years in group A and B, respectively (statistically insignificant (p=0.12). In group A, 96 patients (69.0%) and in group B 92 patients (66.2%) were male while 43 patients (31.0%) in group A and 47 patients (33.8%) in group B were female the difference being statistically insignificant (p=0.608). In group A, 63 (45.3%) patients showed significant reduction in the size of the wound while only 41 (29.5%) patients in group B had adequate wound healing at the end of 04 weeks, the difference being statistically significant (p=0.0064). Conclusion: VAC therapy decreases wound size more effectively than moist wound dressing technique. It definitely reduces hospital stay and ensures early return to work.